Efferent Reader Response Study on Adrian Lyne’s Lolita Movie - Yolanda Tesalonika Danta (Faculty of Language and Literature, University of Surakarta, 2024)
This study examines reader responses to a Lolita movie by Adriane Lyne based on the problem of how people interpret and retain pros and cons in the movie. How viewers' moral frameworks and ethical considerations influence their reader responses to the moral themes depicted in the movie